PENGARUH WAKTU PEMERAHAN TERHADAP BERAT JENIS DAN BAHAN KERING TANPA LEMAK SUSU SAPI FH DI BBPTU-HPT BATURRADEN - Intan Rizkiyani; Susilo Rahardjo; Yanita Viastika; Mulyoto Pangestu (MEDIA PETERNAKAN, 2023)
The research entitled "The Effect of Milking Time on Specific Gravity and Non-Fat Dry Matter of FH Cow's Milk at BPBTU HPT Baturraden" was conducted from 1 to 30 November 2022. The material used in this study was the milk of FH dairy cows at different milking times at BPBTU HPT Baturraden with a sample size of 64 first lactating cows. The method used in this research is a survey method obtained by recording data at BPBTU HPT Baturraden. The data were analyzed using the "z" test. The results of the study proved that the specific gravity content of cow's milk in the morning milking was 3.45%, while the specific gravity content in the afternoon milking was 3.95%. The results of data analysis using the "z" test proved that milking time had no significant effect (P>0.05) on the specific gravity content of cow's milk in BBPTU HPT Baturraden. The non-fat dry matter content of cow's milk in morning milking was 3.14% while the dry matter without fat in cow's milk in the evening milking was 3.11%, the results of data analysis with the "z" test proved that milking time had no significant effect (P> 0.05) to non-fat dry matter of cow's milk. The results of the study concluded that the milking time produced the specific gravity and non-fat dry matter of milk which were relatively the same in the morning and afternoon milking Keyword: FH dairy cows, milk, specific gravity content of milk, milk fat-free dry matter, morning and evening milking.